Rancang Bangun Sistem Informasi Penyewaan Perlengkapan Pernikahan Berbasis Web pada CV. Ria Dewangga - Imam Wibowo; Ardian Fachreza (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
Currently, with the development of information technology, it makes it easier for all industrial sectors, including the rental of wedding instruments. CV. Ria Dewangga Gubug is a company that rents out wedding party equipment. Information media facilities that are still not widespread and rental transactions that are still simple make company information less known to many people. Therefore, it is necessary to have an information system that provides all information and rental transactions that can be reached by the wider community. From the description above, the author is interested in creating a web-based information system design for wedding equipment rental using the waterfall system development method. It is hoped that this system can assist the company in processing customer data, transaction data. In addition, it makes it easier for the public to obtain information and in rental transactions.